2020
DOI: 10.21106/ijma.299
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Year Hospital-Based Retrospective Study of the Predictors of Tuberculosis in People Living with HIV and Receiving Care at Bamenda Regional Hospital, Cameroon

Abstract: Background: Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) co-infections place immense burdens on healthcare systems with particularly diagnostic and therapeutic challenges. TB is high among opportunistic diseases and the most leading cause of death among patients with HIV/AIDS. HIV infection is the most-known risk factor for Mycobacterium tuberculosis infection and progression to active disease, which increases the risk of latent TB reactivation by 20-fold. We present a four-year descriptive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
3
1
0
Order By: Relevance
“…Smoker patients are more likely to be infected with TB compared to non-smoker patients. This result agrees with the result reported by Anye et al based on four year retrospective data of 1077 HIV patients in the Bameda regional hospital of Cameroon [60]. Our result also agrees with report of studies undertaken in Ethiopia [55,59,61].…”
Section: Discussionsupporting
confidence: 94%
“…Smoker patients are more likely to be infected with TB compared to non-smoker patients. This result agrees with the result reported by Anye et al based on four year retrospective data of 1077 HIV patients in the Bameda regional hospital of Cameroon [60]. Our result also agrees with report of studies undertaken in Ethiopia [55,59,61].…”
Section: Discussionsupporting
confidence: 94%
“…It was found that Smoker and alcohol user patients had shorter TB co-infection free survival time than those who are not smoker and non-alcohol users. The result of the study agrees with the result reported by Anye et al based on four year retrospective data of 1077 HIV patients in the Bameda regional hospital of Cameroon 45 . Our result also agrees with report of studies undertaken in Ethiopia 18 , 44 , 46 .…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study and the results of other studies conducted in Ethiopia and other countries indicated that, HIV patients with a lower CD4 counts at a baseline are at a higher risk of co-infection with TB 10 , 18 , 45 . HIV patients with CD4 counts( and 200–349 cell/mm 3 had shorter TB free co-infection survival time.…”
Section: Discussionsupporting
confidence: 67%
“…Tanue et al (35.6%) and Anye et al (36.5%) in this study population reported akin prevalence[26,27]. Nonetheless, a more recent survey conducted in the Central Hospital and Jamot Hospital in Yaoundé, reported a lower TB prevalence (9.1%) among PLHIV[28].…”
mentioning
confidence: 56%